Assessment on Egypt's CSP Components Manufacturing Potential. (May 2015) - Servert, J.F.; Cerrajero, E.
Abstract: A previous study of the World Bank assessed the international competitiveness of five MENA countries, where Egypt showed significant potential to develop several key solar industries. The analysis revealed that Egypt's key strengths on production factors are: low cost of labor and of energy for industrial consumers; availability of glass, steel, and stainless steel; and a strong manufacturing capability and that Egypt's planned deployment of solar energy up to 2020 can be a driver. In this paper, current solar component manufacturing value chains and Egypt's industrial base and potential markets to be served are analyzed to identify the value chains in which Egypt's manufacturing sector could participate. Several solar industries (Heat transfer equipment, Pumping equipment, Mirror, Storage tanks, and Structures) are identified as attractive to be developed in Egypt. A solar component manufacturing industry would lower the cost of the solar plants to be built, increase the country's energy security and contribute to regional renewable energy development. Egypt has the opportunity to enlarge its solar component manufacturing base, which, according to the assumptions in this study, would create up to 3, 000 jobs, most of them in installation activities. Growing solar component manufactures also would increase GDP by over 300 million US$/year; no shortages of materials supply are expected. Energy, on the other hand, might pose a problem, because some of the proposed industries are energy intensive.